Pengaruh Profitabilitas, Ukuran Perusahaan dan Efisiensi Operasional Terhadap Nilai Perusahaan - Nadira Amalia; Adrie Putra (Economic Reviews Journal, 2024)
The purpose of this study is to analyze the profitability, size, and operational efficiency of the company's value. The study uses independent variables such as profitability and size, while the dependent variable is the value of the firm. The research method applied is a quantitative approach with a focus on data analysis. The data used is from a secondary source, namely the company's annual financial reports taken as a sample. The data source used is the official website of Bursa Efek Indonesia, which is http://www.idx.co.id. This research will use the population of companies industry sub sector materials listed on the Indonesia Stock Exchange (BEI) period 2020-2023. The sample-taking method in this study was purposive sampling with 49 companies meeting the criteria out of a total of 103 observations. From the research that has been done, the result is that the profitability, size of the company, and operational efficiency simultaneously affect the growth of profits.